Multiple social credit systems in China - Chuncheng Liu (economic sociology_the european electronic newsletter, 2019)
In 2014, the State Council of the People's Republic of China (State Council) issued a blueprint, the 'Planning Outline for the Construction of a Social Credit System (2014-2020)' (Planning Outline), aiming to build a national social credit system (SCS) in six years. The Planning Outline claimed that many of society's current social problems, from food safety accidents to academic dishonesty, result from the lack of trust and strict regulation of those people who break social trust (xinyong).
Keywords: 300